2009
DOI: 10.1007/s10620-009-0832-2
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Gastric Mucosal Lineages Before or After Acute Oxyntic Atrophy in Gastrin Receptor and H2 Histamine Receptor-Deficient Mice

Abstract: Spasmolytic polypeptide (SP/TFF2)-expressing metaplasia (SPEM) is induced by oxyntic atrophy and is known as a precancerous or paracancerous lesion. We seek to determine whether the gastrin receptor or H(2) histamine receptor influence the development of SPEM. DMP-777 was administered to gastrin receptor and/or H(2) receptor-deficient mice and wild-type mice. Gastric mucosal lineage changes were analyzed. The mucosa from double knockout mice and H(2) receptor knockout mice contained elevated numbers of dual TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Our model established that macrophages promoted the progression of metaplasia, but is not required for metaplasia induction. Efforts to circumvent metaplasia development through manipulation of EGF ligands/receptors (Areg [34], EGFR [34, 35]), endocrine pathways (gastrin [10, 36], histamine [37]) and cytokines (IFNγ [38, 39, 40], IL–11 [41]) have yet to identify factor(s) necessary for the induction of metaplasia in response to parietal cell loss in either an acute drug induced system or chronic Helicobacter infection. Previous studies found that administration of IL-33 is sufficient to induce hypertrophy and mucous metaplasia in the airway, stomach, and intestine through the induction Th2 cytokines and infiltration of myeloid cells and eosinophils [20, 21, 42, 43, 44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…Our model established that macrophages promoted the progression of metaplasia, but is not required for metaplasia induction. Efforts to circumvent metaplasia development through manipulation of EGF ligands/receptors (Areg [34], EGFR [34, 35]), endocrine pathways (gastrin [10, 36], histamine [37]) and cytokines (IFNγ [38, 39, 40], IL–11 [41]) have yet to identify factor(s) necessary for the induction of metaplasia in response to parietal cell loss in either an acute drug induced system or chronic Helicobacter infection. Previous studies found that administration of IL-33 is sufficient to induce hypertrophy and mucous metaplasia in the airway, stomach, and intestine through the induction Th2 cytokines and infiltration of myeloid cells and eosinophils [20, 21, 42, 43, 44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested that large numbers of enteroendocrine cells are present in the fetal human stomach before lineages such as parietal cells and chief cells that develop late in gestation 26. Thus given the extensive projections that are present for most enteroendocrine cells,27 it is tempting to suggest that enteroendocrine cells may be a critical influence for the differentiation of gastric lineages during development as well as during adult life 28 29. Alternatively, concentrations and regionalisation of enteroendocrine cells may coordinate local aspects of gastric physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the expression of AQP4 was reported to be significantly decreased in gastrin knockout mouse compared with wild type and was restored by the supplementation of gastrin . In both PPI‐treated mouse and H 2 R knockout mouse, the plasma level of gastrin was known to be elevated through the acid suppression . Thus, it was suggested that acid suppression might disturb the differentiation process of gastric mucosal epithelial cells including parietal cells and the expression of AQP4 followed by the formation of mucosal hyperplasia through the increase of gastrin.…”
Section: Discussionmentioning
confidence: 99%
“…7 In both PPI-treated mouse and H2R knockout mouse, the plasma level of gastrin was known to be elevated through the acid suppression. 26 Thus, it was suggested that acid suppression might disturb the differentiation process of gastric mucosal epithelial cells including parietal cells and the expression of AQP4 followed by the formation of mucosal hyperplasia through the increase of gastrin. However, long-term acid suppression also leads to the development of SPEM through the decrease of parietal cells and the increase of TFF2positive cells.…”
Section: Discussionmentioning
confidence: 99%